SUSTAINABLE LEADERSHIP TO CREATE SUSTAINABLE ORGANIZATION: IDENTIFY EFFECT FROM PANDEMIC ERA - Januari Ayu Fridayani; Antonius Diksa Kuntara; Stephanus Eri Kusuma (Jurnal Ilmiah Ekonomi Bisnis, 2023)
Leaders must continue to learn and adapt to effectively lead their organizations. Leadership style is a key aspect in ensuring the organization's sustainability, especially after the world suffered from the Covid 19 pandemic. To develop a sustainable company by learning from pandemic occurrences, a new breakthrough in leadership style is required. This article provides a new alternative strategy for leaders in managing their organizations in the context of sustainability. The strategy is obtained from the process of identifying the impact of the Covid 19 Pandemic. Not many Indonesian researchers have considered sustainable leadership styles in studying organizations resilience. The method used is a literature study by identifying changes that arise due to the pandemic. Data analysis was carried out by conducting a critical and thorough study of the related literature and described descriptively. There are three main components need to be considered by the organization to ensure its sustainability: (1) Cultivating core values; (2) Human Resources Management; and (3) Ability to adapt.  (1) Cultivating core values; (2) Human Resources Management; (3) Ability to adapt. Conclusion: Based on these three components, organizations can implement sustainable leadership by “MOVING strategy" (Making value embedded, Orientation to human, Always Adapting) as a form of effort for organizational sustainability that is obtained from learning about the Covid 19 Pandemic